2020
DOI: 10.1002/pc.25696
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of self‐assembled and porous nano titania‐graphene oxide hybrids for toughening the epoxy

Abstract: Nano titania (nTiO 2) aggregated graphene oxide (GO) hybrid nanostructures were successfully prepared by employing 3-(Aminopropyl) triethoxysilane (APTES)-modified nTiO 2 as precursor material. The resulting self-assembled core-shell hybrid structure was observed to have hierarchical porous structure with nTiO 2 forming the core and GO forming the shell in accordance with transmission electron micrographs. The mechanical properties of the hybrid composites were compared with that of individual GO and nTiO 2 lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 55 publications
(51 reference statements)
0
15
0
Order By: Relevance
“…Synthesis of porous and self‐assembled EP/nano titania (TiO 2 )‐GO nanocomposites was performed by Jayan et al [ 146 ] The schematic of the porous core‐shell hybrid structure is presented in Figure 9. This research team reported that the addition of the hybrid nanofillers enhanced the fracture toughness of EP by approximately 200%.…”
Section: Toughening Of Epoxy Resins Using Hybrid Of Carbonaceous Nano...mentioning
confidence: 99%
See 1 more Smart Citation
“…Synthesis of porous and self‐assembled EP/nano titania (TiO 2 )‐GO nanocomposites was performed by Jayan et al [ 146 ] The schematic of the porous core‐shell hybrid structure is presented in Figure 9. This research team reported that the addition of the hybrid nanofillers enhanced the fracture toughness of EP by approximately 200%.…”
Section: Toughening Of Epoxy Resins Using Hybrid Of Carbonaceous Nano...mentioning
confidence: 99%
“…Schematic representation of the porous core‐shell hybrid nano titania‐graphene oxide (TiO 2 ‐GO) structure. [ 146 ] With kind permission from John Wiley & Sons, Inc.…”
Section: Toughening Of Epoxy Resins Using Hybrid Of Carbonaceous Nano...mentioning
confidence: 99%
“…12 . In one of our studies, we have utilized the technique of EDAX to analyze the elements present in the self-assembled nano porous core-shell TiO 2 -GO hybrid material [ 86 ].
Fig.
…”
Section: Characterization Of Superhydrophobic Coatingsmentioning
confidence: 99%
“…The self-cleaning properties were analysed by coating DE, DE/TiO 2 and DE/TiO 2 /rGO on glass substrates. In one of our works, we have made porous titnia-GO hybrids [ 86 ], whose self-cleaning properties are under evaluation. Fan et al [ 109 ] utilized hierarchical nano-needle like arrangements of GO@Cu Silicate for self-cleaning applications.…”
Section: Applicationsmentioning
confidence: 99%
“…The application of polymer-layered nanoparticle composites has been recently increased in engineering structures due to the development of beneficial and functional properties like their high strength-to-weight ratio, corrosion resistance, proper thermal insulation, low thermal expansion, etc. [1][2][3][4] Epoxy resins are among the most widely used substances in the production of polymeric composites. [5][6][7] The mechanical and thermal properties of epoxy resins are related to the microstructure and cross-linked network formed during the curing process.…”
Section: Introductionmentioning
confidence: 99%